Pengaruh Citra Merek Terhadap Niat Pembelian Mobil Honda WR-V dengan Preferensi Konsumen Sebagai Variabel Mediasi dan Demografi Sebagai Variable Kontrol - Dede Mohamad Sandris; Istiharini; Theresia Gunawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study analyzes the influence of Brand Image and Consumer Preference on Purchase Intention of the Honda WR-V, along with the moderating role of demographics in the Greater Jakarta area, Indonesia. A quantitative approach was adopted by collecting primary data through surveys of 315 respondents familiar with the Honda brand and planning to purchase a Honda WR-V within the next year. The survey utilized closed-ended questions and was analyzed using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach. The results indicate that Brand Image has a positive influence on Purchase Intention, both directly and through Consumer Preference. Consumer Preference also significantly influences Purchase Intention. However, demographics do not moderate the relationship between Brand Image, Consumer Preference, and Purchase Intention